THREE-DIMENSIONAL NUMERICAL SIMULATION OF OHMIC HEATING IN FOOD (REMUNOM, 2026)
This work presents three-dimensional numerical simulations of ohmic heating in a homogeneous medium, using a system of coupled nonlinear partial differential equations that describe heat conduction, electric field distribution, and thermal energy generation. The approach adopted considers the dependence of electrical conductivity on temperature. The governing equations were discretized using the Finite Difference Method with second-order approximations in a uniform mesh, using a fully implicit scheme. The analyses revealed an almost linear temperature increase, with greater intensity in the central region of the domain, where there is a higher electric current density. Volumetric heat generation was also concentrated in the center, following the gradients of the electric potential. The results obtained were consistent with previous studies and reinforce the reliability of the model for applications involving rapid, uniform, and controlled heating in conductive systems.